Acesso aos serviços de Atenção Primária à Saúde pelos usuários de uma ilha: desafios e potencialidades - Santos, Quezia Nunes Frois dos (2025)
Introduction: Universal, free, equal, and comprehensive access to health services in Brazil is a right guaranteed by the 1988 Federal Constitution, which established the Unified Health System (SUS). Access to services offered in Primary Health Care (PHC) can be related to the various access possibilities and can be influenced by the location of the health unit, the availability of days and times, meeting spontaneous demand, and the population's understanding of these aspects, whether or not it meets their needs. Objectives: To analyze how access to PHC services has been configured by users of a Family Health Unit (FHU) located on an island; To identify the challenges and potential in accessing PHC services experienced by users of a FHU located on an island; and To develop a service flowchart for users of a FHU located on an island, which will be disseminated in a pamphlet. Methodology: This is a qualitative, exploratory, and descriptive study conducted at the Paramana Family Health Strategy (FHS) hospital in Ilha dos Frades, Salvador, Bahia. Participants included five health professionals and four health service managers, ten users, and two leaders working at the Paramana Family Health Strategy (FHS) facility. Data collection was conducted using semistructured interviews, and thematic content analysis was used. Because this study involved human participants, it complied with the precepts of Resolution 466/2012 and Resolution 510/2016 and was submitted to the Research Ethics Committee for review. Results: Access to services at a FHS hospital located on an island has unique characteristics, strongly influenced by the geographic and social context of the territory. Among the potential advantages of this process, the proximity between health professionals and the community stands out. Among the challenges, geographic isolation poses barriers to mobility, making travel to the mainland more complex, time-consuming, and, in some cases, costly. Reliance on water transportation, such as speedboats and SAMU (Mobile Emergency Care) vessels, makes access to urgent and emergency care more vulnerable to weather conditions and resource availability, resulting in delays and limitations. Furthermore, the difficulty in obtaining appointments for specialized consultations and exams is noteworthy. Another challenge identified concerns interpersonal relationships and community dynamics. This study also resulted in the creation of an analytical flowchart that depicts the configuration of access for users of a USF (Family Health Unit) located on an island. Final considerations: In summary, PHC in hard-to-reach areas proves to be a space for close and personalized care, with the potential to strengthen bonds and continuity of care. However, logistical limitations, the scarcity of specialized resources, and social and cultural barriers pose challenges that require integrated management, transportation, and communication strategies to ensure equitable and efficient access to healthcare.